Melindungi hak pekerja, membangun good corporate governance : solusi bagi kemelut di PT Dirgantara Indonesia. - Komnas HAM (Indonesia) (Jakarta : Komisi Nasional Hak Asasi Manusia, 2005)
Human rights violation in the settlement of labor dispute in PT Dirgantara Indonesia, a national aircraft industry in Indonesia.
Includes index.
"Desember 2005."
Mode of access: Internet.
Keywords: Dirgantara Indonesia, PT; Human rights -- Indonesia; Arbitration, Industrial -- Indonesia